Development of Lifelong Education in the Republic of Croatia: An Analysis of Trends in PhD Graduations - Ivana Vrdoljak (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
This research thoroughly examines the development and present condition of lifelong education in the Republic of Croatia, with a particular emphasis on the patterns related to individuals who have obtained a PhD degree. This study encompasses data at both the national level and country-specific levels, facilitating a comprehensive analysis of regional discrepancies and patterns. Moreover, this study differentiates data based on gender, providing insights into gender-related patterns within higher education. The initial results indicate diverse growth rates among counties, and significant gender differences were observed. The discussion pertains to improving lifelong education and ensuring equal educational opportunities for all individuals in Croatia, considering the consequences of the findings above. This paper provides a significant resource for policymakers, educators, and stakeholders interested in the continued development and improvement of Croatia's education system.
Keywords: I21; I23; J16; 330; lifelong education; Republic of Croatia; PhD; gender; social sciences; economy